Relationship between caryopsis morphological characteristics and fusarium ear rot in corn - Costa, Raquel Silva; Môro, Fabíola Vitti; Môro, José Roberto; Silva, Herberte Pereira da; Panizzi, Rita de Cássia (Pesquisa Agropecuaria Brasileira, 2003)
Fusarium ear rot of corn caused by Fusarium moniliforme is responsible for severe yield losses. Probably fungal penetration in the caryopsis takes place at the silk scar and is related to the level of infection and the morphological characteristics of the caryopsis. The objective of this work was to identify morphological characteristics that confer resistance to the fungus in caryopsis of corn. Caryopsis of six lines of corn, with and without inoculation with the pathogen, were evaluated using a stereomicroscope and scanning electron microscope. Morphological characteristics of the caryopsis such as tegument with saliences and reentrances accentuated, pericarp no much thick, starch less compact and presence of the silk canal favor the penetration of F. moniliforme.